Model Strategi Pengembangan Sosial Radio Komunitas dalam Mitigasi Bencana Di Kawasan Gunung Kelud - Anam Miftakhul Huda (Universitas Muhammadiyah Ponorogo, 2019)
This study reviewed about the importance of the existence of community radio in disaster-prone areas to maintain the existence of this radio, this community radio conducts social development, specifically in the field of disaster mitigation and information for surrounding communities. The existence of community radio is important as a means of various informations and to strengthen brotherhood in the community. Jangkar Kelud community radio is mass media engaged in broadcasts in the kelud area, namely in Blitar Regency, Malang Regency and Kediri Regency, this radio was formed by a group of people in the Kelud area, the problem is the death threat of the existence of radio station. It is useless when disaster no longer occurs, but the benefits of community radio are not when a disaster occurs but radio as a disaster mitigation media are very important continuously to convey awareness to the community. This type of research is descriptive qualitative, by adopting observations, interviews and documentation. The results of this study are, the strategy of building familiarity between residents and the Jangkar Kelud Community, Strategy to Build External Support, Disaster Learning Strategies from an Early Age because it is assets to instill the caring sosil value in the Kelud Mountain area from early childhood.